The Routledge companion to mobile media art - Hjorth, Larissa; Silva, Adriana de Souza e; Lanson, Klare (Routledge, 2020)
"In this companion, a diverse, international, and interdisciplinary group of contributors and editors examine the rapidly expanding, far-reaching field of mobile media as it intersects with art across a range of spaces-theoretical, practical and conceptual. As a vehicle for, and of, the everyday, mobile media is recalibrating the relationship between art and digital networked media, and reshaping how creative practices such as writing, photography, video art and filmmaking are being conceptualized and practised. In exploring these innovations, The Routledge Companion to Mobile Media Art pulls together comprehensive, culturally-nuanced and interdisciplinary approaches; considerations of broader media ecologies and histories and political, social, and cultural dynamics; and critical and considered perspectives on the intersections between mobile media and art. This book is the definitive publication for researchers, artists, and students interested in comprehending all the various aspects of mobile media art, covering digital media and culture, internet studies, games studies, anthropology, sociology, geography, media and communication, cultural studies and design"- Resumé vydavatel
Keywords: digitální média; digitální umění; digital media; digital art; elektronické knihy; sborníky; electronic books